2018
DOI: 10.1080/09670262.2018.1513571
|View full text |Cite
|
Sign up to set email alerts
|

Rapid colour changes inEuglena sanguinea(Euglenophyceae) caused by internal lipid globule migration

Abstract: The accumulation of red pigments, frequently carotenoids, under chronic stress is a response observed in diverse kinds of eukaryotic photoautotrophs. It is thought that red pigments protect the chlorophyll located underneath by a light-shielding mechanism. However, the synthesis or degradation of carotenoids is a slow process and this response is usually only observed when the stress is maintained over long periods of time. In contrast, rapid colour changes have been reported in the euglenophyte Euglena sangui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 45 publications
(49 reference statements)
0
11
0
Order By: Relevance
“…This conversion cycle was initially termed the violaxanthin cycle. Since a special role emerged for zeaxanthin in allowing plants to cope with high light, this cycle is frequently referred to as the xanthophyll cycle, along with other xanthophyll cycles that interconvert xanthophyll epoxides to epoxide-free xanthophylls [17,[20][21][22][23]. In his foreword to a review on "In vivo functions of carotenoids in higher plants" [24], Norman Krinsky wrote, "Almost 40 years ago, David Sapozhnikov and his associates from Russia first described In his foreword to a review on "In vivo functions of carotenoids in higher plants" [24], Norman Krinsky wrote, "Almost 40 years ago, David Sapozhnikov and his associates from Russia first described the light-induced deepoxidation of the plant carotenoid epoxide, violaxanthin to non-epoxide derivatives, and the reversal of the process in the dark.…”
Section: Carotenoid Biosynthesis and Biochemical Control Of Xanthophymentioning
confidence: 99%
See 1 more Smart Citation
“…This conversion cycle was initially termed the violaxanthin cycle. Since a special role emerged for zeaxanthin in allowing plants to cope with high light, this cycle is frequently referred to as the xanthophyll cycle, along with other xanthophyll cycles that interconvert xanthophyll epoxides to epoxide-free xanthophylls [17,[20][21][22][23]. In his foreword to a review on "In vivo functions of carotenoids in higher plants" [24], Norman Krinsky wrote, "Almost 40 years ago, David Sapozhnikov and his associates from Russia first described In his foreword to a review on "In vivo functions of carotenoids in higher plants" [24], Norman Krinsky wrote, "Almost 40 years ago, David Sapozhnikov and his associates from Russia first described the light-induced deepoxidation of the plant carotenoid epoxide, violaxanthin to non-epoxide derivatives, and the reversal of the process in the dark.…”
Section: Carotenoid Biosynthesis and Biochemical Control Of Xanthophymentioning
confidence: 99%
“…This conversion cycle was initially termed the violaxanthin cycle. Since a special role emerged for zeaxanthin in allowing plants to cope with high light, this cycle is frequently referred to as the xanthophyll cycle, along with other xanthophyll cycles that interconvert xanthophyll epoxides to epoxide-free xanthophylls [ 17 , 20 , 21 , 22 , 23 ].…”
Section: Carotenoid Biosynthesis and Biochemical Control Of Xanthomentioning
confidence: 99%
“…Therefore, it is speculated that citrus grown in the fall and winter has a high photoprotection ability at high PPFD, and this hybrid may adjust the path of energy flow absorption using heat quenching. Laza-Martínez et al [42] revealed that xanthophyll cycle-associated photoprotection supports plant photosynthetic productivity and survival in environments with unique combinations of environmental factors. In our study, ETR was useful for the nondestructive estimation of Pn and NPQ, since these indices were significantly and positively correlated with ETR when exposed to 0~1200 PPFD (Figure 4) and 1200~2000 PPFD with SC (Figure 5B) and with NT in spring, fall, and winter (Figure 5A).…”
Section: Discussionmentioning
confidence: 99%
“…Euglena sanguinea is a flagellated, unicellular algae found in high nutrient containing freshwaters (Ohio, 2013;Cimoli, 2014;Mandal et al, 2016Mandal et al, , 2018. The occurrence of red colour is due to presence of carotenoid astaxanthin pigments in the cytoplasm (Grung & Liaaen-Jensen, 1993;Gerber & Häder, 1994;Frassanito et al, 2008;Laza-Martínez et al, 2019, Zheng et al, 2020. The reddening process includes the relocation of cytoplasmic lipid globules where astaxanthin accumulates from the center of the cell to peripheral locations when exposed to high light (Laza-Martínez et al, 2019)frequently carotenoids, under chronic stress is a response observed in diverse kinds of eukaryotic photoautotrophs.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of red colour is due to presence of carotenoid astaxanthin pigments in the cytoplasm (Grung & Liaaen-Jensen, 1993;Gerber & Häder, 1994;Frassanito et al, 2008;Laza-Martínez et al, 2019, Zheng et al, 2020. The reddening process includes the relocation of cytoplasmic lipid globules where astaxanthin accumulates from the center of the cell to peripheral locations when exposed to high light (Laza-Martínez et al, 2019)frequently carotenoids, under chronic stress is a response observed in diverse kinds of eukaryotic photoautotrophs. It is thought that red pigments protect the chlorophyll located underneath by a light-shielding mechanism.…”
Section: Introductionmentioning
confidence: 99%